THE ROLE OF NERVES IN MAINTAINING OF GASTRODUODENAL STRUCTURE AND FUNCTIONS - Сулаєва, О.М. (World of Medicine and Biology, 2015)
Gastrointestinal pathology takes one of the leading places in the morbidity rate. A long-time comprehensive study has helped in determining the spectrum of exogenous and endogenous pathological factors that are associated with gastroduodenal pathology. It can be stated, that issues of digestive system regulation has been in focus of scientist for more than two centuries. Nevertheless, pathogenesis of such disorders as gastroesophageal reflux disease, gastritis, peptic ulcer disease, duodenitis is still not clear. Structural homeostasis and functions of gastroduodenal area (GDA) are controlled by neural link, specific gastrointestinal regulatory peptides that have endo-, paraand neuroendocrine effects; and local factors – cytokines, growth factors, nitric oxide, etc. These regulatory molecules are produced by various cells of the mucosa and neurons of intramural ganglia. The auto-regulation, synchronicity, sequence, integration and protection of digestive organs are achieved due to the potentiation and modulation of these molecules. At the same time there is a hierarchy of GDA regulatory mechanisms, due to which any disorder automatically activates higher levels of management and control, that’s why neuro-endocrine control goes on the forefront. Initially, the centers of autonomic nervous systems are activated that leads us to the aim of this review to fully analyze the structural organization of the parasympathetic innervation and role of vagus nerve in the pathology and compensatory-adaptive processes in GDA. Vagus nerve dependent gastric reflexes are mediated through vagal afferent fibers synapsing upon neurons of the nucleus tractus solitarius which, in turn, modulates the preganglionic parasympathetic dorsal motor nucleus within the medullary dorsal vagal complex. These centers establish connection with the different parts of hypothalamus and cerebral cortex, providing the integration of metabolic control mechanisms, water-salt metabolism, digestion, and hemodynamics. Vagal efferents are associated with neurons of the intramural ganglia in submucosa and musclularis externa, controlling contraction of smooth myocytes and secretion of glandular cells. We focused on understanding the cause-and-effect relationships of gastroduodenal pathology and want to clarify the role of vagus nerve. It is, however, important to start with physiology of digestive process, which includes three phases: cerebral, gastric and intestinal. Regulation of secretion includes the cerebral phase that is mainly vagal with participation of some hormones. Experiments with false feeding, similar to the Pavlov’s classic experiment, have shown that, in addition to the vagus nerve stimulation, the level of several gastric hormones was significantly increased. The intensity of cerebral phase depends on multiple settings: activation of conditioned reflexes by the sense of smell and taste receptors of the tongue, and mechanical stimulation of the stomach and intestine chemoreceptors. Afferents activation of the gastroduodenal mucosa leads to the switching on of vago-vagal reflexes that impact on the motility, mucus and secretion of the digestive juices and cytoprotection in GDA. The role of vagus nerve in maintaining the structural and functional homeostasis of gastroduodenal is deliberated in the review. The following issues are discussed: characteristics of the afferent vagal nerves in the gastroduodenal area; the effect of vagal afferents in the adaptive response of the gastric and duodenal mucosa; regulation of mucus and acid production by vagal efferent fibers; feedback mechanisms in the control of acid production. Despite the fact that the vagus nerve is a powerful stimulator of the production of hydrochloric acid, it is also determine the activation of cytoprotective mechanisms adapting different structures of gastroduodenal mucosa to peptic factors impact.
Keywords: gastroduodenal area; vagus nerve; acetylcholine